Pengaruh Pemberian Jenis dan Dosis Pupuk Organik Cair Terhadap Pertumbuhan dan Produksi Tanaman Cabai Merah (Capsicum annum L.) - Wahyuni Wahyuni; Adrianus Adrianus; Amelia A Limbongan (Universitas Musamus, Merauke, Papua, 2018)
The research was aims to determine the effect of giving types and doses of organic liquid fertilizer on red chili plants. The use of the right type and dosage of fertilizer will affect the production of red chili plants better. The method used in this study used a factorial Randomized Block Design (FRBD) with the treatment of 2 types of fertilizers and 3 different doses of fertilizer then combined, so that there were 6 test treatments. The study was conducted 3 times, so we got 18 units of experimental design. The results showed that the interaction between treatment types and doses of organic liquid fertilizer did not have a real effect on all variables observed for growth components such as plant height and number of branches, but had a significant effect on the observed variables of production components, namely the total sample of fruit plants, sample crop production, and production per plot, with the type treatment and fertilizer dosage of 10 ml / liter of water.